2017
DOI: 10.1039/c7ta06644a
|View full text |Cite
|
Sign up to set email alerts
|

Constructing noble-metal-free Z-scheme photocatalytic overall water splitting systems using MoS2 nanosheet modified CdS as a H2 evolution photocatalyst

Abstract: A noble-metal-free Z-scheme system was constructed for photocatalytic overall splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(64 citation statements)
references
References 65 publications
0
62
0
Order By: Relevance
“…However, not all the semiconductors can meet the band structure requirements of photocatalytic over‐all water splitting. The emergence of 2D semiconductors with special advantages has brought a turn for the photocatalytic over‐all water splitting . For example, Zhu and coworkers constructed a new artificial BP/BiVO 4 Z‐scheme photocatalytic system that can be applied in overall pure‐water splitting without any sacrificial agents and external bias under visible light irradiation.…”
Section: Energy and Environment Applicationsmentioning
confidence: 99%
“…However, not all the semiconductors can meet the band structure requirements of photocatalytic over‐all water splitting. The emergence of 2D semiconductors with special advantages has brought a turn for the photocatalytic over‐all water splitting . For example, Zhu and coworkers constructed a new artificial BP/BiVO 4 Z‐scheme photocatalytic system that can be applied in overall pure‐water splitting without any sacrificial agents and external bias under visible light irradiation.…”
Section: Energy and Environment Applicationsmentioning
confidence: 99%
“…One strategy to circumvent this is to combine photo‐absorbers with MoS 2 . Recent studies have shown that MoS 2 has been combined with semiconductor‐based light absorbers such as Si, organic, and inorganic dyes for photoelectrochemical HER . However, all of these systems lacked a linkage/tether between the dye and the MoS 2 HER catalyst, and were simply formed by mixing/physisorption, thus limiting the electronic communications between dye and catalyst, and thus inhibiting the light‐driven HER efficiency.…”
Section: Figurementioning
confidence: 99%
“…The past decades have witnessed the use of molybdenum disulfide (MoS 2 ), a 2D lamellar material with excellent conductive property, as electrocatalysts and photocatalysts for applications in electrochemical and solar-to-fuel conversion (Xiang et al, 2012; Dai et al, 2017; Yang et al, 2017). It was confirmed that the combination of MoS 2 with functional semiconductors enabled obvious enhancements in both photocatalytic and electrocatalytic hydrogen production activity (Sun et al, 2016; Zhang et al, 2016; Iqbal et al, 2017; Yuan et al, 2017). The hybridization of MoS 2 with Ag 3 PO 4 to produce MoS 2 /Ag 3 PO 4 composite materials has been primarily explored, however the application is restricted to the photodegradation of different kinds of organic pollutants (Wang L. et al, 2015; Wang P. F. et al, 2015; Gyawali and Lee, 2016; Li et al, 2016; Zhu et al, 2016; Wan et al, 2017), the employment of MoS 2 /Ag 3 PO 4 nanocomposites as photocatalysts for solar-light-driven oxygen evolution from water splitting has not yet been explored.…”
Section: Introductionmentioning
confidence: 89%